System design for social intervention : improving throuhg interior design the client’s experience and staff productivity - Burzynska, Klaudia Karolina, 1990- (2016)
Santa Casa de Misericordia is an organization, whose mission is to treat and support the sick and disabled, as well as assist “exposed ones”. Principally, it is recognizable by its social services. Big matters of society are social exclusion, loneliness, managing unemployment, etc. At some point of our lives we will all need some kind of level of care. By intervention is destined any program, service, policy, or product that is intended to eventually influence or change people´s social, environmental, and organizational conditions as well as their choices, attitudes, beliefs, and behaviors. Social care interventions tend to be compound, programmatic and dependent. They occur through investigation and analysis and discovering solutions at the end. To achieve this, there is a need to select, adapt and evaluate given information and apply it to present environment. This dissertation aims to create physical surroundings that are “psychologically supportive”, where a significant relationship exists between a client and organization. Different features are studied, in order to achieve a matching solution and interior design guides to create a specific type of space. There is scientific evidence, that poor design works in contradiction of the well being of clients of social services, also its employees. The second part of this study is based on existing facility located in Rua das Janelas Verdes. It is a base for project, helping to understand the space and relationships occurring there. I have used methods of Evidance Based Design and a questionnaire to collect primary data. By changing the interior design of this facility, it was intended to improve mostly patient´s experience with Santa Casa de Misericordia, but also the employees. Improving facilities image may help clients enjoy better the service and help the employees cope better with workplace stress and to provide a better service, while outcomes will rise. Current design and floor plans were investigated and studied. Its exploration, observation and analysis led me to significant solutions and conclusions. Environmental factors do have an influence, on how service is perceived but its clients. Not only clients, but also employees are always a part of it. Interior and exterior surroundings have impact on all human beings. Textures, lights, nature and art have individual responses and the majority of respondeds believed that the social care environment had a direct influence on well-being, productivity and coping with stress